Early holistic scoring of writing: a theory, a history, a reflection - Haswell, Richard, author; Elliot, Norbert, author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
During the educational accountability movement of the 1980s/1990s, holistic scoring became known as the fairest and most efficient ways to assess writing performance. Addressing the history of holistic assessment in the UK and US (1930s to mid- 1980s) they conceptualize reinterpreting the history while re-envisioning its future.--Provided by publisher.
Nine maps -- Two premises -- Holistic scoring and Great Britain, 1936-1949 -- Great Britain after 1949 -- Paul Diederich and advanced placement holistic scoring, 1954-1980 -- Osmond Palmer, Fred Godshalk, and the English composition test, 1960-1972 -- California schools, 1960-1982 -- Independent researchers, 1960-1980, and the National Assessment of Educational Progress, 1969-1984 -- What does a score mean? -- Reconsiderations.
Keywords: Composition (Language arts) -- Ability testing; Educational tests and measurements